ANALISIS KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS XI MIPA SMA NEGERI 3 PADANG DALAM MENYELESAIKAN SOAL MATERI BARISAN DAN DERET TAHUN PELAJARAN 2019/2020 - Nidya Milano (Jurnal Edukasi dan Penelitian Matematika, 2022)
This research was conducted to analyze one of the students’ mathematical problem-solving abilities that have not shown good results. Analyzing the problem-solving abilities of students in class XI MIPA 7 on the answer sheets for the material on Rows and Series. The type of research used is descriptive with a qualitative approach. Based on the research that has been done, three analysis results were obtained. First, high-ability participants have moderate problem-solving abilities, with a score of 8 (66,67%) in good predicate on geometric series question and a score of 9,7 (80,83%) in good predicate on Decay problem. Second, moderately capable participants have moderate problem-solving abilities, obtaining a score of 7,87 (65,58%) on a moderate predicate on Geometric Series question and a score of 7,56 (63%) with a moderate predicate on Decay problem. Third, low-ability students have problem-solving abilities in the moderate category tend to be low, obtaining a score of 7,078 (58,98%) in moderate predicate on Geometric Series question and a score of 4,1 (34,16%) with a poor predicate on Decay problem.Keywords  Problem Solving skills, Sequence and Series, Decay Problem